Analysis of Slope Stability of Small and Medium Earth-rock Dams underSeepage-stress Coupling and Fluctuation of Reservoir Level - SU Zhengyang; ZHANG Zhitao; LI Hanzhang (Renmin Zhujiang, 2020)
In order to study the influence mechanism and law of seepage-stress coupling and thefluctuation of reservoir level on slope stability of small and medium homogeneous earth-rock dams,according to the principle of unsaturated seepage and the simplified Bishop method of rigid bodylimit equilibrium theory, this paper carries out the finite element simulation of seepage andstability of upstream and downstream slopes of homogeneous earth-rock dam under the conditions ofseepage-stress coupling, and sudden rise and sudden drop of reservoir level. The results showthat: Based on the effect of seepage stress coupling, when the reservoir level rises sharply,the safety factor of the upstream dam slope firstly increases rapidly, then slowly, and finallyremains stable, while that of downstream dam slope firstly decreases, then slowly increases, andfinally tends to be stable; When the reservoir level drops sharply, the safety factor ofupstream dam slope firstly decreases rapidly, then slowly, and finally remains stable, while thatof the downstream dam slope firstly increases constantly, then slowly decreases, and finally tends to be stable; In the process of sudden rise and sudden drop of water level, the safety factorof upstream and downstream dam slopes is greater than the minimum safety factor stipulated by thecode, and their anti-sliding stability meets the requirements of the code. The research resultsprovide a reference for risk assessment of small and medium earth-rock dams and danger eliminationand reinforcement measures for reservoir dams in the later stage.